2021
DOI: 10.1098/rsbl.2021.0023
|View full text |Cite
|
Sign up to set email alerts
|

Larval habitats impose trait-dependent limits on the direction and rate of adult evolution in dragonflies

Abstract: Natural selection on juveniles is often invoked as a constraint on adult evolution, but it remains unclear when such restrictions will have their greatest impact. Selection on juveniles could, for example, mainly limit the evolution of adult traits that mostly develop prior to maturity. Alternatively, selection on juveniles might primarily constrain the evolution of adult traits that experience weak or context-dependent selection in the adult stage. Using a comparative study of dragonflies, I tested these hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…In contrast to sexual ornaments that continue to develop in adults (e.g. Grether, 1996; Guillermo‐Ferreira et al, 2014; Moore, 2021), the size of the white wing band and wing tip cannot be augmented in adults, nor can individuals make them brighter because wax cannot be added to the wing after emergence (Gorb et al, 2009). Therefore, the only time an individual can invest in this signal is before emergence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to sexual ornaments that continue to develop in adults (e.g. Grether, 1996; Guillermo‐Ferreira et al, 2014; Moore, 2021), the size of the white wing band and wing tip cannot be augmented in adults, nor can individuals make them brighter because wax cannot be added to the wing after emergence (Gorb et al, 2009). Therefore, the only time an individual can invest in this signal is before emergence.…”
Section: Discussionmentioning
confidence: 99%
“…These field guides report the range between the maximum and minimum phenotypic values for each species based on scientific accounts, handbooks by local experts and direct measurements of collected specimens. Following many previous studies (Waller et al, 2019; Moore, 2021; Svensson et al, 2023; Hersch & Moore, 2023), we recorded the mid‐point of the reported ranges for rear wing length and body length as our species‐level trait values. We then calculated a species' relative wing size by dividing a species' log e ‐transformed rear wing length by its log e ‐transformed body length.…”
Section: Methodsmentioning
confidence: 99%
“…The discovery of abundant genetic (co-)variation was thought to undergird Darwin's assertion because such genetic resources should be sufficient for each life-cycle stage to eventually adapt to its unique selective pressures when given enough time (reviewed in [2]). However, recent empirical and theoretical studies indicate that even highly polygenic traits have not evolved as independently between life-cycle stages as we have long assumed [3][4][5][6][7][8]. For instance, evolution towards smaller body sizes is associated with the evolution of smaller adult sizes in frogs, despite the potential for substantial post-metamorphic growth [4].…”
Section: Introductionmentioning
confidence: 93%
“…Several population sex ratios were duplicated across the two datasets and were therefore included only once here. Following other recent studies [7,20,27], I examined iNaturalist observations of the species to assess if males of the species possess dark pigmentation within any of their wing cells.…”
Section: (B) Data Compilationmentioning
confidence: 99%